The projection questionnaire-design, use and utility - Bilić, Vedran (Array, 1998)
Projection is a widespread mechanism of defence. It is an important issue in a number of anthropological researches. o estimate changes in inensity and flexibility of the projection a measuring instruments is unavoidable. Material: To standarise the questionnaire answer of 250 examinees were used, They were divided in two independent groups. Group I consisted of 125 patients treated at Clinic for Psychological Medicine and Group 2 of 125 students in the third year of the Medical Faculty in Zagreb. Methods: To process the results a statistical package SPSS was used. A chi(2) test was employed and tables of contingency were made. A factor analysis of The Projection Questionnaire was employed and varimax rotation separated five factors which characteristic roots were greater than one. Results: A new instrument for measuring the projection, The projection Questionnaire is developed and standardised. A considerable use of the projection by normal population is confirmed.